Altered Sympathetic-to-Immune Cell Signaling via β2-Adrenergic Receptors in Adjuvant Arthritis. (1st October 2013) - Lorton, Dianne; Bellinger, Denise L.; Schaller, Jill A.; Shewmaker, Eric; Osredkar, Tracy; Lubahn, Cheri
Abstract : Adjuvant-induced arthritic (AA) differentially affects norepinephrine concentrations in immune organs, and in vivo β -adrenergic receptor ( β -AR) agonist treatment distinctly regulates ex vivo cytokine profiles in different immune organs. We examined the contribution of altered β -AR functioning in AA to understand these disparate findings. Twenty-one or 28 days after disease induction, we examined β 2 -AR expression in spleen and draining lymph nodes (DLNs) for the arthritic limbs using radioligand binding and western blots and splenocyte β -AR-stimulated cAMP production using enzyme-linked immunoassay (EIA). During severe disease, β -AR agonists failed to induce splenocyte cAMP production, and β -AR affinity and density declined, indicating receptor desensitization and downregulation. Splenocyte β 2 -AR phosphorylation (p β 2 -AR) by protein kinase A (p β 2 -ARPKA ) decreased in severe disease, and p β 2 -AR by G protein-coupled receptor kinases (p β 2 -ARGRK ) increased in chronic disease. Conversely, in DLN cells, p β 2 -ARPKA rose during severe disease, but fell during chronic disease, and p β 2 -ARGRK increased during both disease stages. A similar p β 2 -AR pattern in DLN cells with the mycobacterial cell wall component of complete Freund's adjuvant suggests that pattern recognition receptors (i.e., toll-like receptors) are important for DLN p β 2 -AR patterns. Collectively, our findings indicate lymphoid organ- and disease stage-specific sympathetic dysregulation, possibly explaining immune compartment-specific differences in β 2 -AR-mediated regulation of cytokine production in AA and rheumatoid arthritis.